Evaluating the efficiency of grain boundary serrations in attenuating high-temperature hot corrosion degradation in Alloy 617. (1st April 2019) - Bhuyan, P.; Pradhan, S.K.; Mitra, R.; Mandal, S.
Graphical abstract: Highlights: Two-step heat treatment led to the formation of serrated boundaries in Alloy 617. Extended ageing treatment resulted in higher fraction (˜77%) of serrated boundaries. Percolation of S and O led to enrichment of elements in the as-received specimen. GBS microstructure alleviates hot corrosion by hindering the percolation of S and O. GBS specimen exhibited markedly reduced damage even after extended hot corrosion. Abstract: The influence of grain boundary serrations (GBS) on high-temperature hot corrosion in Alloy 617 was critically investigated by immersing both the as-received and GBS specimens in the salt mixture comprising of 75% Na2 SO4 + 20% NaCl + 5% V2 O5 at 1273 K for 24 h. The GBS microstrucure, realized through scheduled thermal treatment, exhibited enhanced resistance to corrosion damage against the as-received condition. On account of GBS, the diffusion of percolating elements through grain boundaries and subsequent enrichment/depletion of alloying elements is significantly restricted. More impressively, the serrated microstructure exhibited markedly reduced damage even after prolonged hot corrosion test (48 h).